Political Segmentation Voters of Local Political Contests in Bulukumba, Indonesia - Bahri, Syamsul; Harakan, Ahmad (Pusat Penelitian Ilmu Sosial dan Humaniora Kontemporer, 2022)
The objective of this research is to address the posed problem by examining the outcomes of the political segmentation of voters in the 2020 Bulukumba Regency local elections. The utilized research methodology is descriptive qualitative. The present study employs observation, interviews, and documentation as research instruments to elucidate the Political Segmentation of Voters Winning Pairs of Simultaneous Local Elections in Bulukumba Regency in the year 2020. The study's informants comprised individuals such as Candidates for Regent and Deputy Regent, Political Consultants, Leaders of the Winning Team, and members of the Community. The findings of this investigation suggest that the political segmentation of voters, as conducted by researchers, is based on interviews conducted with team leaders and candidate pairs before the election of the Regent of Bulukumba. The discussions centered on the superior programs that have been conveyed by the incumbent regent, with a particular emphasis on the welfare of the middle class. The equitable distribution of policies implemented by the government has resulted in the participation of various social classes, including those from the agricultural sector and fishermen, in the Bulukumba district. Additionally, the current administration has continued to pursue previously established government programs that were previously unrealized.